En motivforskydning : F. C. Bredahls mindetavle i Taulov Kirke - Bach-Nielsen, Carsten (Kirkehistoriske Samlinger, 1992)
In the village church of Taulov near Fredericia there is a memorial ablet that has been restored in 1729 by F.C.Bredahl, owner of the near-by manorhouse Søholm. The painting depicts a naked human who is oppressed by the tables of the law. By its sides John the Baptist and Moses are seen. John lifts up the tables and thereby easens the burden of the law for the human. John the Baptist points in the direction of the lamb on top of Mount Zion. The model for this painting is a title-engraving of one of the many unauthorized hymnals of the 1700th century, C.Cassube’s En ny fuldkommen Dansk Psalme-Bog... from 1666. By examining the engraving it can be stated that the local painter has changed its subject. In the engraving Paul stands to the right, but the unknown painter obviously has been very familiar with the Lutheran postreformation iconography in which Moses is commonly seen as opposed to John the Baptist. In Lutheran iconography this is the usual way to express the relationship between law and gospel. According to this traditional mode of expression, the painter has altered the figure of Paul to the figure of Moses. The theme of the engraving is man’s salvation from the law through the gospel. In the painting of the memorial tablet the theme has changed according to Galathians 3,24 and now teatches the beholder, that the law is our schoolmaster to bring us unto Christ.